PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR TEMATIK - Yuslinda Putri Kusumaningrum; Nyoto Hardjono (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to improve the activity and learning outcomes by applying the Discovery Learning learning model. This Classroom Action Research was carried out in grade 4B of Salatiga 06 State Elementary School in Salatiga City. Data collected includes activities and learning outcomes, teacher observations, student observations. Data collection techniques carried out in this study are observation models, documentation models, and test models. This research was carried out in two cycles. Each cycle includes 6 (six) stages, namely (1) Stimulation (Stimulation); (2) Problem Identification; (3) Data Collection (Data Collection); (4) Data Processing; (5) Verification; (6) Interesting Conclusions. In this study it is said to be successful if at least 80% of students get a value of ≥ 75. The results of the study show: (1) the score of pre-cycle activity in grade 4B is 72% and the score of pre-cycle student learning is 58.06%; (2) Student learning completeness in cycle I is 68% and in cycle II is 84% ​​(3) Student activity score in cycle I is 70% and in cycle II is 82.50%. From the data above clearly shows that in the first cycle learning outcomes have not met expectations which means that the indicators of success have not been achieved while in cycle II learning outcomes are in line with expectations which means that the indicators of success have been achieved.